2009
DOI: 10.1186/1471-2121-10-19
|View full text |Cite
|
Sign up to set email alerts
|

The cell nuclei of skeletal muscle cells are transcriptionally active in hibernating edible dormice

Abstract: Background: Skeletal muscle is able to react in a rapid, dynamic way to metabolic and mechanical stimuli. In particular, exposure to either prolonged starvation or disuse results in muscle atrophy. At variance, in hibernating animals muscle atrophy may be scarce or absent after bouts of hibernation i.e., periods of prolonged (months) inactivity and food deprivation, and muscle function is fully preserved at arousal. In this study, myocytes from the quadriceps muscle of euthermic and hibernating edible dormice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 40 publications
6
39
0
Order By: Relevance
“…This suggests that demethylation as a regulatory mechanism must involve wider genomic regions. At the very least, the genomic hypomethylation observed within the muscle represents a molecular rearrangement that is supported by the overall transcriptional activity observed in the skeletal muscle of hibernating mammals (Malatesta et al, 2009). This needs to be explored in the future with full genomic mapping of DNA methylation over different hibernation stages.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that demethylation as a regulatory mechanism must involve wider genomic regions. At the very least, the genomic hypomethylation observed within the muscle represents a molecular rearrangement that is supported by the overall transcriptional activity observed in the skeletal muscle of hibernating mammals (Malatesta et al, 2009). This needs to be explored in the future with full genomic mapping of DNA methylation over different hibernation stages.…”
Section: Discussionmentioning
confidence: 99%
“…Here again, hibernation typically results in relatively minor changes in fiber CSA, with most studies showing a reduction of only 0-10% (mean change of −4.4% for type I fibers and −2.4% for type II fibers) associated with hibernation (Andres- Cotton and Harlow, 2010;Deveci and Egginton, 2002a;Gao et al, 2012;Hershey et al, 2008;Lee et al, 2008Lee et al, , 2010Malatesta et al, 2009;Tinker et al, 1998). However, at the extremes, a few studies have shown reductions in fiber CSA of between −30% and −55% (Agostini et al, 1991;Steffen et al, 1991).…”
Section: Morphological Changes During Hibernationmentioning
confidence: 99%
“…It has also been reported that follistatin increases satellite cell proliferation, possibly by blocking myostatin (Gilson et al, 2009). A recent study reported no change in muscle fibre shape and size or fibre type during hibernation (Malatesta et al, 2009). Furthermore, they also reported that nuclear and mitochondrial activity is maintained during deep torpor (measurement of one time point during hibernation).…”
Section: N E Brooks K H Myburgh and K B Storeymentioning
confidence: 99%
“…Despite long periods of inactivity, large hibernators such as bears appear to avoid protein loss and maintain muscle functional capacity (Harlow et al, 2001;Lohuis et al, 2007). This phenomenon is not peculiar to bears, as resistance to atrophy is also found in golden-mantled ground squirrels (Rourke et al, 2004a;Rourke et al, 2004b), dormice (Malatesta et al, 2009) and lower vertebrates such as turtles (McDonagh et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation